2019
DOI: 10.1108/jhass-08-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

On financial development and economic growth in Egypt

Abstract: Purpose This paper aims to discuss the evolution of the Egyptian banking sector and the main trends in financial development in Egypt. The purpose of this study is to examine empirically the relationship between the development of the financial sector and economic growth in Egypt between 1980 and 2016. Design/methodology/approach The paper draws comparisons based on critical financial indicators between Egypt and selected emerging markets and developing economies. It uses a new data set of financial developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Guru and Yadav (2019) using growth indicators of the stock market and banking sector for a panel of most developing economies including Brazil, Russia, India, China, and South from 1993 to 2014, found that the impact of the developed nancial system on economic growth is positive and statistically signi cant. Using data of Egypt on nancial progress indicators and economic development from 1980 to 2016, Mohieldin et al (2019) employed econometric modeling of bivariate regression to investigate the association between nancial progress and economic growth in Egypt. They revealed that both nancial development indicator that is money supply and Index of Financial Markets Access have a strong association with real income growth whereas there is no signi cant association between e ciency of and access to banking services and real income growth.…”
Section: Financial Development and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Guru and Yadav (2019) using growth indicators of the stock market and banking sector for a panel of most developing economies including Brazil, Russia, India, China, and South from 1993 to 2014, found that the impact of the developed nancial system on economic growth is positive and statistically signi cant. Using data of Egypt on nancial progress indicators and economic development from 1980 to 2016, Mohieldin et al (2019) employed econometric modeling of bivariate regression to investigate the association between nancial progress and economic growth in Egypt. They revealed that both nancial development indicator that is money supply and Index of Financial Markets Access have a strong association with real income growth whereas there is no signi cant association between e ciency of and access to banking services and real income growth.…”
Section: Financial Development and Economic Growthmentioning
confidence: 99%
“…A robust nancial isnfrastructure leads to the growth of businesses and thereby generation of more employment and income (Sehrawat and Giri 2016). Recently, many researchers empirically investigated that nancial development positively explains the economic growth of a country (Guru and Yadav 2019, Masoud and Hardaker 2012, Mohieldin et al 2019, Puatwoe and Piabuo 2017and Sehrawat and Giri 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, many EMDEs have relatively large populations and young age structure but still suffer from income disparities and significant poverty levels. While those countries have great potential to use their population structure and create demographic dividends (Nassar et al, 2017), many still suffer from weak financial institutions and capital markets that are incapable of channeling the dividends of their demographic windows and leveraging (Mohieldin et al, 2019) but also put more pressure on debt sustainability. Using external debt as the prime source of finance increases such risks.…”
Section: Emerging Markets and Developing Economiesmentioning
confidence: 99%
“…Egypt represents a crucial emerging market, where the banking sector owns a large number of financial assets compared to other financial institutions. Thus, it is considered as a setting dominated by financial institutions (Mohieldin et al, 2019). We choose Egypt to be our case of emerging markets, as Egypt is considered one of the most resilient economies compared to other emerging markets, which survived the global financial crisis and a massive political/ economic distress [2].…”
Section: Jhassmentioning
confidence: 99%